La Soudière des Trois Lucs (Marseille) - Etudes historiques et fouilles préliminaires - Gilles Olive (L'Atelier du CRH, 2012)
The supplying of vegetable soda was interrupted in 1808 after Napoleon’s army had entered Spain. Therefore, (artificial) soda factories using Nicolas Leblanc’s patent from 1791 opened mainly in Paris, Rouen and Marseille between June 1808 and the end of 1810. In Marseille, one of these factories was set up in 1810 in the district called Les Trois Lucs. Thanks to everything that could have been discovered, it was perfectly located, thus allowing the preliminary excavations